2022
DOI: 10.3390/electronics11081254
|View full text |Cite
|
Sign up to set email alerts
|

Information Separation Network for Domain Adaptation Learning

Abstract: The Bai People have left behind a wealth of ancient texts that record their splendid civilization, unfortunately fewer and fewer people can read these texts in the present time. Therefore, it is of great practical value to design a model that can automatically recognize the Bai ancient (offset) texts. However, due to the expert knowledge involved in the annotation of ancient (offset) texts, and its limited scale, we consider that using handwritten Bai texts to help identify ancient (offset) Bai texts for handw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…In comparison to the subterranean scenes, abundant annotated point cloud data exist in the road scenes. It is observed that domain adaptation has the ability to transfer knowledge from the annotated scenes to the unannotated scenes [5,6]. Therefore, exploring an effective domain adaptive subterranean 3D pedestrian detection method for accurate 3D pedestrian detection in the target domain subterranean scenes requires further research.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to the subterranean scenes, abundant annotated point cloud data exist in the road scenes. It is observed that domain adaptation has the ability to transfer knowledge from the annotated scenes to the unannotated scenes [5,6]. Therefore, exploring an effective domain adaptive subterranean 3D pedestrian detection method for accurate 3D pedestrian detection in the target domain subterranean scenes requires further research.…”
Section: Introductionmentioning
confidence: 99%